2014
DOI: 10.1186/1471-2296-15-3
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards prescribing cognitive enhancers among primary care physicians in Germany

Abstract: BackgroundPrimary care physicians are gate keepers to the medical system having a key role in giving information and prescribing drugs to their patients. In this respect they are involved in claims of patients/clients for pharmacological Cognitive Enhancement (CE). Therefore, we studied the knowledge of primary care physicians about CE and their attitudes toward prescribing CE drugs to healthy subjects.MethodsA self-report paper-and-pencil questionnaire and case vignettes describing a hypothetical CE drug were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…Franke et al (2014) confirmed these findings in a paper and pencil questionnaire study among 832 German physicians. In both studies, physicians worried about misuse and deemed PCE for young people to be unnecessary.…”
Section: Medical Safetymentioning
confidence: 74%
See 1 more Smart Citation
“…Franke et al (2014) confirmed these findings in a paper and pencil questionnaire study among 832 German physicians. In both studies, physicians worried about misuse and deemed PCE for young people to be unnecessary.…”
Section: Medical Safetymentioning
confidence: 74%
“…Furthermore, 212 US American and Canadian physicians, reported in an online survey, being less comfortable prescribing PCE substances for non-medical use to young adults, compared to older patients (Banjo et al, 2010 ). Franke et al ( 2014 ) confirmed these findings in a paper and pencil questionnaire study among 832 German physicians. In both studies, physicians worried about misuse and deemed PCE for young people to be unnecessary.…”
Section: Medical Safetymentioning
confidence: 74%
“…Consequently, pNE applicants either purport a fictive medical need to the attending physician or directly consult their doctors for prescription of pharmacological neuroenhancers. The latter was reported by 40.8% of general practitioners [ 112 ]. It should be stated again that from a prescriptive point of view, these cases should not exist, and doctors should not service these accessibility strategies.…”
Section: Availability/accessibility Of Pnementioning
confidence: 99%
“…I Europa er forskning i IMRMK temmelig begraenset. Gennem de seneste fem år har enkelte, hovedsageligt survey-baserede, studier (Schelle et al, 2015;Maier et al, 2013;Lengvenyte & Strumila, 2016;Middendorff et al, 2012;Eickenhorst et al, 2012;Franke et al, 2014) dog vist, at IMRMK også forekommer i Europa. Disse studier indikerer en stigning i IMRMK om end i mindre omfang end i USA.…”
Section: Baggrundunclassified